Potential of Stimuli-Responsive Star Polymer for Cancer Targeting - Patihul Husni; Muhammad Alvien Ghifari; Norisca Aliza Putriana (Universitas Padjadjaran (Unpad), 2020)
Application of stimuli-responsive star polymers in cancer targeting and drug delivery has been extensively researched because of their several advantages in comparison with their linear counterparts. Functionalization and recombination of various arm architectures of the star polymer are very possible to be conducted to suit various needs. The star polymers could not only load more therapeutic drug due to more arms than linear polymers but also be functionalized with targeted moieties for more targeted delivery. Furthermore, the chains in star polymers could be regulated to produce stimuli-responsive star polymer for cancer targeting. The review article aimed to describe the benefits of star polymers and the types of stimuli-responsive delivery system for cancer targeting. Over the last decade, stimuli-responsive star polymers for cancer targeting using either internal stimuli (e.g., pH, redox, enzyme, hypoxia) or external stimuli (e.g., thermal, ultrasound, light, magnetic) has garnered immense interest for researchers. Possibility to mimic a complex natural phenomenon could be achieved by incorporating various stimuli-responsive functionalities in the star polymer.